2022
DOI: 10.3389/fbioe.2022.992069
|View full text |Cite
|
Sign up to set email alerts
|

Single-step rapid chromatographic purification and characterization of clinical stage oncolytic VSV-GP

Abstract: Purification of viruses, especially for therapeutic purposes, is a tedious and challenging task. The challenges arise due to the size and surface complexity of the virus particles. VSV-GP is a promising oncolytic virus, which has been approved for phase I clinical trials by the Food and Drug Administration (FDA) of United States and Paul Ehrlich Institute (PEI) of Germany. The virus particles of VSV-GP are larger in size than vectors commonly used for gene therapy (e.g., adenovirus, adeno-associated virus, etc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…VSV-GP virus batches were produced in HEK-293F cells in either shaker flask or bioreactor formats (depending on batch ID). After infecting cells at an MOI of 0.0005, virus was purified from clarified harvest via centrifugation and/or chromatographic methods similar to previous reports (58, 59). The downstream processes employed were slightly unique for each batch (for example the use of different purification columns or formulations).…”
Section: Methodsmentioning
confidence: 99%
“…VSV-GP virus batches were produced in HEK-293F cells in either shaker flask or bioreactor formats (depending on batch ID). After infecting cells at an MOI of 0.0005, virus was purified from clarified harvest via centrifugation and/or chromatographic methods similar to previous reports (58, 59). The downstream processes employed were slightly unique for each batch (for example the use of different purification columns or formulations).…”
Section: Methodsmentioning
confidence: 99%
“… 181 Similarly, research tested a IFN-II-engineered VSV variant and found that, compared with VSV, the virus can inhibit cancer and improve immune reaction by decreasing tumor infiltration of Tregs and enhancing tumor infiltration of CTLS. 182 It is worth noting that oncolytic VSV expressing IFN-II is presently in clinical tests on solid tumor, 183 which has broad development prospects ( Table 3 ).…”
Section: Use Of Ov and Ifn Tampering In The Treatment Of Crcmentioning
confidence: 99%